Spatiotemporal Characteristics of Offshore Wind Energy Availability in the China Seas and Adjacent Waters over the Past Several Decades - Yunuo Liu; Qinghong Li; Ruizhe Shen; Fenghua Zhang; Zhengming Qiao; Lei Wang (Journal of Marine Science and Engineering, 2026)
Current wind energy planning in the China Seas and adjacent waters generally focuses on wind speed or wind power density (WPD), yet lacks sufficient understanding of the long-term climatic evolution patterns and climatic driving mechanisms of effective wind speed occurrence (EWSO) and its correlation with climate oscillations. Based on the ERA5 10 m sea surface wind reanalysis data from the European Centre for Medium-Range Weather Forecasts (ECMWF) and multiple key climate index datasets from 1941 to 2020, this study systematically analyzed spatiotemporal distribution characteristics, long-term variation trends, and correlations with climate oscillations of EWSO in the China Seas and adjacent waters. The results indicated the following: (1) There are discrepancies between the distribution of EWSO and mean wind speed. (2) Over the past 80 years, EWSO across the study area has shown an overall significant increasing trend with pronounced regional disparities, among which the Yellow–Bohai Sea area has exhibited a significant decreasing trend. (3) The interannual variability of EWSO is regulated by climate oscillations such as ENSO. This study demonstrates that incorporating EWSO as an independent indicator separate from wind speed into the wind energy resource assessment system is crucial for identifying offshore wind power generation risks and more accurately evaluating the actual operational duration of wind farms in China’s offshore waters and adjacent sea areas. The correlation between EWSO and climate oscillations such as ENSO provides an important scientific basis for improving seasonal prediction models of wind energy resources.